UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE ROTATING TRIO EXCHANGE (RTE) - Fatkhan Amirul Huda; Adpriyadi Adpriyadi; Ika Yulianti (JUTECH : Journal Education and Technology, 2020)
ABSTRACTThe purpose of this research was to improve student’s learning motivation and learning outcomes through Rotating Trio Exchange (RTE) Type of Cooperative Learning Model in fourth-grade students of Sekolah Dasar Negeri 14 Mengkurai in academic year 2018/2019. Research form was classroom action research which conducted in two cycles.. Data collecting used observation sheets, questionnaire sheets and test questions. Classroom action research results showed that through the Rotating Trio Exchange (RTE. Students learning motivation in the first cycle of overall questions was given, the result was 88.57%. In the second cycle of the overall questions given, the results were 95.71%. While student’s cognitive learning outcomes in the first cycle obtained an average value of 69.29 and the second cycle obtained an average value of 91.43 so that an average increase was 22.14. The effective learning results in the first cycle were 71.43%, and the second cycle was 87.86%, while the psychomotor learning outcomes in the first cycle were 87.14% and the second cycle was 97.14%. The student responses results in the first cycle and the second cycle showed students were very interested and enthusiastic so it can be concluded that there is an improvement in student motivation and learning outcomes through Rotating Trio Exchange (RTE) Type of Cooperative Learning ModelKeywords: Cooperative Learning (RTE). Learning Motivation andLearning Outcome ABSTRAKTujuan penelitian ini adalah untuk meningkatkan motivasi belajar dan hasil belajar siswa melalui model pembelajaran Cooperative Learning Tipe Rotating Trio Exchange (RTE) pada siswa kelas IV Sekolah Dasar Negeri 14 Mengkurai tahun ajaran 2018/2019. Bentuk penelitian ini adalah penelitian tindakan kelas yang diaksanakan dalam dua siklus. Untuk mengumpulkan data digunakan lembar observasi,lembar angket dan soal tesMotivasi belajar siswa pada siklus I dari keseluruh pertanyaan yang diberikan diperoleh hasil 88,57%. Pada siklus II dari keseluruhan pertanyaan yang diberikandiperoleh hasil sebesar 95,71%. Sedangkan hasil belajar kognitif siswa pada siklus I diperoleh nilai ratarata 69,29 dan pada siklus II diperoleh nilai rata-rata sebesar 91,43 sehingga diperoleh peningkatan rata-rata sebesar 22,14.Hasil belajar afektif pada siklus I di peroleh hasil sebesar 71,43%, dan siklus II sebesar 87,86%, Sedangkan hasil belajar psikomotorik siklus I sebesar 87,14% dan siklus II sebesar 97,14%. Hasil respon siswa pada siklus I dan siklus II siswa sangat tertarik dan antusias Sehingga dapat disimpulkan bawah terdapat peningkatan motivasi dan hasil belajar Volume 1, Nomor 1, Juni 2020 22 siswa dengan menggunakan model pembelajaran Cooperative Learning Tipe Rotating Trio Exchange (RTE)Kata Kunci: Motivasi belajar, Hasil belajar Cooperative Learning (RTE)